Degradation of low rank coal by Rhizopus oryzae isolated from a Pakistani coal mine and its enhanced releases of organic substances. (1st October 2019) - Sabar, Muhammad Adnan; Ali, Muhammad Ishtiaq; Fatima, Noreen; Malik, Aneela Younas; Jamal, Asif; Farman, Muhammad; Huang, Zaixing; Urynowicz, Michael
Abstract: Coal bio-transformation technologies can convert the neglected low rank coal reserves to alternative fuels and non-fuel organic chemicals. Fungal mediated coal degradation can serve as biological beneficiation for alternative substances. For enhanced biodegradation, fungi can be isolated from coal environments and optimized for coal degradation processes. In this study, an indigenous fungal isolate AD-1, identified as Rhizopus oryzae by fungal ITS sequences, was isolated from a low rank coal sample collected from Darra Adam Khel, Frontier Region Kohat, Pakistan. The AD-1 mediated coal degradation was optimized and showed a substantial release of organics at 1.5% glucose and 0.5% coal loading ratio within 11 days. The GC–MS analysis of the black liquid from coal solubilization showed a variety of organic compounds including aromatic acids, fatty acids, alkanes, amines, and amides. The depolymerized liquid extract was analyzed by High-Performance Size-Exclusion Chromatography (HPSEC) for determining the molecular mass distribution of the released organics. The release of the organic fragments had molecular mass distribution ranging between 1.5 kDa and 26.7 kDa. In addition, the released fraction and residual coal sample after solubilization were analyzed with Fourier transform infrared spectroscopy (FT-IR) to explore the structural changes aroused by the AD-1 fungal treatment. The AD-1 fungal strain has the abilities of decarboxylation and deamination, as well as breaking the side chains of the aromatic rings. This demonstrates that indigenous fungi from coal environments can enhance the biodegradation and shows a potential for producing chemical feedstock or alternative fuels from low rank coal.